RESULTS OF PRE-ECLAMPSIA TREATMENT AT THAI NGUYEN A HOSPITAL (Tạp chí Y học Cộng đồng, 2026)
Faced with the reality that pregnant women with preeclampsia were coming to Thai Nguyen A Hospital for treatment to determine treatment outcomes, we conducted a study with the following objectives: to evaluate the treatment outcomes of preeclampsia in pregnant women at Thai Nguyen A Hospital. Research subjects and methods: Including 136 pregnant women with preeclampsia treated from January 2023 to the end of December 2024. Results: 100% of pregnant women had their pregnancies terminated. The method of terminating pregnancies by cesarean section accounted for 88.2%, and 11.8% of pregnant women had normal births. All cases were terminated within 24-48 hours of admission to the hospital, so the rate of complications among mothers and newborns was low. There were 30 cases of premature birth in severe preeclampsia, 26 cases with 19.1%. There were no cases of postnatal death. 100% of pregnant women discharged from the hospital were healthy and normal.
Keywords: Preeclampsia, preeclampsia treatment results.